Prevention and Management of Infectious Complications of Percutaneous Interventions - Huang, Steven Y.; Philip, Asher; Richter, Michael D.; Gupta, Sanjay; Lessne, Mark L.; Kim, Charles Y. (Seminars in Interventional Radiology, 2015)
Infectious complications following interventional radiology (IR) procedures can cause significant patient morbidity and, potentially, mortality. As the number and breadth of IR procedures grow, it becomes increasingly evident that interventional radiologists must possess a thorough understanding of these potential infectious complications. Furthermore, given the increasing incidence of antibiotic-resistant bacteria, emphasis on cost containment, and attention to quality of care, it is critical to have infection control strategies to maximize patient safety. This article reviews infectious complications associated with percutaneous ablation of liver tumors, transarterial embolization of liver tumors, uterine fibroid embolization, percutaneous nephrostomy, percutaneous biliary interventions, central venous catheters, and intravascular stents. Emphasis is placed on incidence, risk factors, prevention, and management. With the use of these strategies, IR procedures can be performed with reduced risk of infectious complications.
Keywords: complication; infection; catheter-related; interventional radiology